Analisis Efektivitas Aplikasi ‘Super Apps’ dalam Proses Pendaftaran Turnamen Olahraga di KONI Kabupaten Tangerang - Irsyad Taufiq Ilham Supardi; Binastya Anggara Sekti (Prosiding SISFOTEK, 2024)
This study aims to evaluate the effectiveness of the "Super Appsb " application in facilitating the registration process for prospective participants in sports tournaments organized by KONI Kabupaten Tangerang. The application is designed to address various obstacles in manual registration, such as time constraints, data input errors, and slow processes. The evaluation is conducted using quantitative methods to measure user satisfaction, system effectiveness, and the application's impact on the number of registrants and the time required to complete the registration process. Data is collected through surveys involving 200 prospective participants who have used the application to register for sports tournaments. Quantitative data analysis is performed using descriptive statistics and regression tests to examine the relationship between the application's ease of use and levels of satisfaction and registration effectiveness. The results indicate that the "Super Apps" application significantly simplifies the registration process, reduces data errors, and accelerates registration time. User satisfaction is also high, with the majority of respondents stating that the application is more efficient compared to manual registration methods. This study provides recommendations for further development of the application in terms of user interface and the integration of additional features that can enhance user experience